The prevalence of mental health disorders in Type 2 diabetic women in Amol, Iran - Shabnam Omidvar; Fatemeh Nasiri Amiri; Farzan Kheyrkhah; Fatemeh Bakouei (Babol University of Medical Sciences, 2015)
Introduction: Chronic diseases, diabetes in particular, are globally epidemic, and are regarded as a major public health problem for reproductive health. Diabetes may influence maternal health, pregnancy outcomes, and also mental health.  The aim of the current study was to identify the prevalence of mental health disorders in type 2 diabetic women and to evaluate the possible correlation of the subscales of mental disorders with coexisting diabetic complications. Methods: In this cross-sectional study, a total number of 400 women with type 2 diabetes were selected from the outpatient clinic of diabetic care center in Amol, Iran. The General Health Questionnaire (GHQ-28) was used as a screening tool for the detection of mental disorders.  The questionnaire, which contained 28 items, comprised four domains: somatic symptoms, anxiety /insomnia, social dysfunction, and severe depression. The diabetic complications were obtained from their documents. Results: The mean age of the participants, with a mean diagnosed 8.9±0.3 years, was 48.8±0.5 years. The prevalence of mental disorder among Type 2 diabetic women was found to be 73.7%. The most prevalent mental health disorder was social dysfunction (78.8), somatic symptoms (51.7%), anxiety/ insomnia (33.3%), and severe depression (11.3%) among type 2 diabetic women.   The prevalence of mental health disorder was higher in women with coexisting diabetic complications&ge3 than those <3 complications (p <0.05).  Significant differences was found between somatic symptoms, anxiety/ insomnia with coexisting diabetic complications (p <0.05). There were no significant differences between social dysfunction, severe depression with coexisting diabetic complications. Conclusion: The study demonstrated the importance and the effect of diabetes on mental health disorders. Therefore, it is necessary to put emphasis on the benefits of psychological screening at outpatient clinic of diabetic care center in Iran, particularly for those with co-morbid medical complications.